Integration and Harmonization Strategy in Multicultural Society at Palu City - Haslinda B. Anriani (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2018)
This research reveals the strategy of the people in Palu City in realizing the integration and harmonization among those with diverse cultural backgrounds. This research has an important position considering the conflict that had taken place in Palu City. Therefore, qualitative research was conducted via in-depth interviews in Palu City community, selecting the main informants from the two major ethnic groups, namely Kaili ethnic as indigenous ethnic and Buginese ethnic as ethnic migrants. The informants asked several questions about the social interaction between the local ethnic and the ethnic migrants and their socio economic and political lives. This interview technique was supported by observation and literature studies related to this research problem. The data was then analyzed descriptively qualitative. The result of the research shows: (1) Palu City community is open to multiculturalism, (2) integration strategy is done in the form of joint activities at Rukun Tetangga (RT, neighbourhood, is the lowest administrative division of Indonesia under Rukun Warga/RW)/Rukun Warga (RW, hamlet) level such as Cleaning Saturday, Sport and Art Contest in RT/RW level, RT/RW gathering, (3) the government cooperates with society to realize social harmony in Palu City.